Far East Scarlet-Like Fever Caused by a Few Related Genotypes of Yersinia pseudotuberculosis, Russia - Timchenko, Nelly F. (Emerg Infect Dis, 2016)
We used multivirulence locus sequence typing to analyze 68 Yersinia pseudotuberculosis isolated in Russia during 1973–2014, including 41 isolates from patients with Far East scarlet-like fever. Four genotypes were found responsible, with 1 being especially prevalent. Evolutionary analysis suggests that epidemiologic advantages could cause this genotype’s dominance.